Bundle sheath chloroplast volume can house sufficient Rubisco to avoid limiting C4 photosynthesis during chilling - Pignon, Charles P (Journal of experimental botany, 2019)
C4 leaves confine Rubisco to bundle sheath cells. Thus, the size of bundle sheath compartments and the total volume of chloroplasts within them limit the space available for Rubisco. Rubisco activity limits photosynthesis at low temperatures. C3 plants counter this limitation by increasing leaf Rubisco content, yet few C4 species do the same. Because C3 plants usually outperform C4 plants in chilling environments, it has been suggested that there is insufficient chloroplast volume available in the bundle sheath of C4 leaves to allow such an increase in Rubisco at low temperatures. We investigated this potential limitation by measuring bundle sheath and mesophyll compartment volumes and chloroplast contents, as well as leaf thickness and inter-veinal distance, in three C4 Andropogoneae grasses: two crops (Zea mays and Saccharum officinarum) and a wild, chilling-tolerant grass (Miscanthus × giganteus). A wild C4 Paniceae grass (Alloteropsis semialata) was also included. Despite significant structural differences between species, there was no evidence of increased bundle sheath chloroplast volume per leaf area available to the chilling-tolerant species, relative to the chilling-sensitive ones. Maximal theoretical photosynthetic capacity of the leaf far exceeded the photosynthetic rates achieved even at low temperatures. C4 bundle sheath cells therefore have the chloroplast volume to house sufficient Rubisco to avoid limiting C4 photosynthesis during chilling